A study of migraine cases in a tertiary care hospital neurology outpatient department: demography, sub classification and clinical features - C., Selvaraj; S., Sivakumar (International Journal of Research in Medical Sciences, 2018)
Background: Recurrent headache disorders impose a substantial burden on headache sufferers, family and society. In India, 15 to 20% of people suffer from migraine with an adult female: male ratio of 2:1. This study has been done with an aim at documenting the different types of migraine, their clinical presentations among patients presented to the Headache clinic, Neurology outpatient Department, Government Rajaji Hospital, Madurai during a one year period. Methods: The patients registered at Headache clinic, Neurology outpatient Department, Government Rajaji Hospital, Madurai during one year period between the March 2009 and February 2010 with the diagnosis of migraine as per International Headache Society 2004 criteria were taken for this study. The clinical material was collected from the records and by patient interviews with a detailed pre-prepared proforma. The various parameters of the patients were compared, classified and analysed with specific reference to national and international studies. Results: Migraine is the commonest type of headache comprising of about 76% of total cases of headache. Migraine without aura (48%) was more common than migraine with aura (32%). Female preponderance was noticed in all subtypes of migraine, age of onset being in 2nd and 3rd decade for majority of the subgroups of migraine, with positive family history in 45% of cases, with predominant unilateral in presentation and temporal in location, lasting for 12 to 24 hours in majority of cases. Conclusions: Migraine is the commonest type of headache in patients observed in this study. Among subtypes migraine without aura is the commonest. Second and third decade is the commonest age group of onsets.